Correlation of Imprint and Crush cytology with Bronchoscopic biopsy in the diagnosis of Bronchogenic carcinoma - Karki, Pratikchya; Neupane, Samir; Dhungana, Ashesh; Tiwari, Sumida (Nepalese Journal of Cancer, 2021)
Introduction: Lung carcinoma is the most common cancer with 2.1 million (11.6%) newly diagnosed cases in 2018. Over the years, many cytotechniques have been developed but their combination with histology is still an area of controversy. Imprint and crush cytology are considered simple, rapid and cost effective for a low resource setting in the early diagnosis and management of lung cancer. Here, we aimed to assess the diagnostic accuracy of imprint and crush cytology and compare them with histopathology. Method: A prospective study was conducted from May 2017 to April 2018 at the Pulmonary medicine unit and Department of Pathology at National Academy of Medical Sciences (NAMS), Bir Hospital. A total of 53 patients were enrolled in the study who showed visible mass on bronchoscopy. Three to five bits of tissue were obtained, imprint and crush smear were prepared from them and the tissue were then sent for histopathological examination. The level of significance selected was p < 0.005. Results: The most common age group affected was 60-69 years. 91% cases were smokers, with a male predominance. The most common location of endobronchial growth was left upper lobe. 43 cases were malignant in biopsy. The sensitivity, specificity, accuracy and positive predictive value of imprint cytology was 71.05%, 87.50%, 73.91% and 96.43% respectively while that for crush cytology was 74.36%, 75%, 74.47% and 93.55% respectively. The diagnostic yield of imprint, crush smear and forceps biopsy were 52.8%, 58.4% and 81.1% respectively. Squamous cell carcinoma was the most common carcinoma in this study. Conclusion: Imprint and crush cytology yield additional information that can be complementary to endobronchial biopsy. They are convenient, do not burden the patients and thus can be carried out wherever possible during bronchoscopy.